Lenin and the twentieth century : a Bertram D. Wolfe retrospective - Wolfe, Bertram D.; Gerson, Lennard D.; Besançon, Alain (Stanford : Hoover Institution Press, 1985)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Lenin, Vladimir; 20e eeuw; Sovjet-Unie.